(untitled) (Al-Qamar, 2022)
Allama Muhammad Iqbal, an eminent poet and philosopher of South Asia became a source of stimulation in the 20th century among the Muslim ummah because of his revolutionary ideological poetry. He emphasized self-realization for the comprehension of Divine strength within humanity. His inspirational philosophical discourse left enormous influence on the younger generation of his time and on the bases of his nationalistic ideology, the creation of Pakistan became possible. He is considered to be the national poet of Pakistan and his ideologies provided the Pakistani artists of the formative period with inspiring theoretical frameworks which were expressed through visual representation. Art being an essential part of humanity, reflects the ideological, religious and socio-political settings of a society and in Pakistan, art also focuses on multiple conceptual panoramas. Artists like Abdur Rehman Chughtai, Sadequain and Aslam Kamal illustrated the philosophical references of Iqbal’s poetry in direct yet symbolic manner with a reason to focus on the underlying stimulating context for inspiring the younger generation of Pakistan. In contemporary Pakistani art, his philosophy of K̲h̲udī has also been revisited as a reference to instigate a novel chapter of meaningful existence analyzing the contemporary challenges faced by the nation of Pakistan mainly after 9/11.